2013
DOI: 10.5430/afr.v2n3p142
|View full text |Cite
|
Sign up to set email alerts
|

The Composition and Compensation of the Board of Directors as Predictors of Corporate Fraud

Abstract: We test whether the composition and compensation of the board of directors are related to fraudulent corporate behavior. We use Accounting and Auditing Enforcement Releases from 2003 through 2010 to form a sample of 128 firms with violations and compare the characteristics of their boards to a matched sample of 128 control firms. SEC violations are less likely when the board has more women, independent members, and financial experts. Fraud is also less likely when director tenure is shorter and when the CEO is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 43 publications
4
26
2
Order By: Relevance
“…Performance-based compensation will align directors' and shareholders' interests and will also provide information about the fact that more attention to shareholder value maximization reinforces the role of the board in preventing EM. A similar conclusion on the alignment approach is reached by Kim, Roden and Cox [13], who suggest that greater cash-based compensations are used to attract quality directors, as well as to establish a better agency relationship between directors and shareholders than equity-based compensation.…”
Section: Introductionsupporting
confidence: 60%
“…Performance-based compensation will align directors' and shareholders' interests and will also provide information about the fact that more attention to shareholder value maximization reinforces the role of the board in preventing EM. A similar conclusion on the alignment approach is reached by Kim, Roden and Cox [13], who suggest that greater cash-based compensations are used to attract quality directors, as well as to establish a better agency relationship between directors and shareholders than equity-based compensation.…”
Section: Introductionsupporting
confidence: 60%
“…To test the quad model, a researcher would focus on a specific domain or form of governance failure -such as financial fraud, excessive CEO compensation, or acquisition overpayments -and generate a sample of firms that vary on this outcome measure (possibly using matched-pairs, state-based sampling, or random sampling (e.g., Harris & Bromiley, 2007;Kim et al, 2013)). Next, the researcher would need to develop operationalizations of the four elements of the quad model, guided by prior research or new insights (including from our Table 1), and then code for the presence vs. absence of each quality in each director (in the period leading up to the observed outcome).…”
Section: Testing the Modelmentioning
confidence: 99%
“…The results of the study by Cumming et al (2014) found negative relationship between gender diversity and securities fraud and indicated that the increase number of women in the boardroom decreases the occurrence of securities fraud. The results of the study by Kim, Roden & Cox (2013) presented a negative relationship between gender diversity and corporate fraud. The results of the study by Gavious, Segef & Yosef (2012) posited a negative relationship between the presence of female directors and earnings management.…”
Section: Gender Diversitymentioning
confidence: 91%
“…The results of the study by Xu, Zhang & Chen (2018) found that board age is negatively related to the likelihood of corporate financial fraud. The results of the study by Kim et al (2013) posited a negative relationship between age and the likelihood of fraud. On the contrary, the results of the study by Hasnan et al (2016) found that the effects of board characteristics on financial restatements in Malaysia fail to document a statistically significant association for board age.…”
Section: Board Age Diversitymentioning
confidence: 98%
See 1 more Smart Citation